Improving the Quality of Requirements with Refactoring - Ramos, Ricardo; Piveta, Eduardo K.; Castro, Jaelson; Araújo, João; Moreira, Ana; Guerreiro, Pedro; Pimenta, Marcelo S.; Price, R. Tom (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2007: Anais do VI Simpósio Brasileiro de Qualidade de Software, 2007)
Requirements specification can often exhibit some shortcomings, regarding contents and organization of its partial specification elements. Sometimes, modularization is deficient, with modules dealing with too much information, or the same functionality being specified in different modules. Left unchecked, these inadequacies will propagate themselves to the subsequent phases of the software development and cause problems during maintenance. We have been able to identify a collection of typical deficiencies in the specification of structured documents and we propose a collection of refactorings that minimize or remove them. Doing this early in the development process increases requirements modularity and understandability. A case study is conducted to illustrate the use of these refactoring practices on two existing requirement documents.